Cinderella: hello friend (Hello friend India, 2010)
Cinderella, a kind young woman mistreated by her stepmother and stepsisters, dreams of attending the royal ball. With the help of her fairy godmother, she transforms and captures the prince's heart. When the magic fades, her lost slipper leads to a happy reunion.